2010
DOI: 10.1111/j.1469-0691.2009.02836.x
|View full text |Cite
|
Sign up to set email alerts
|

Body site colonization in patients with community-associated methicillin-resistant Staphylococcus aureus and other types of S. aureus skin infections

Abstract: Efforts to control spread of community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) are often based on eradication of colonization. However, the role of nasal and non-nasal colonization in the pathogenesis of these infections remains poorly understood. Patients with acute S. aureus skin and soft tissue infection (SSTI) were prospectively enrolled. Each subject's nasal, axillary, inguinal and rectal areas were swabbed for S. aureus and epidemiological risk factors were surveyed. Among the 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
117
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(130 citation statements)
references
References 20 publications
7
117
6
Order By: Relevance
“…We considered whether diaper rash or younger age in patients wearing diapers were associated with CA-MRSA infection, but there were few diaper rashes in our study population and no relationship between age and infections in the groin or buttock area. The association between infections in the buttock or groin area and CA-MRSA may be due to other factors that facilitate colonization of MRSA over MSSA [30].…”
Section: Continuedmentioning
confidence: 99%
“…We considered whether diaper rash or younger age in patients wearing diapers were associated with CA-MRSA infection, but there were few diaper rashes in our study population and no relationship between age and infections in the groin or buttock area. The association between infections in the buttock or groin area and CA-MRSA may be due to other factors that facilitate colonization of MRSA over MSSA [30].…”
Section: Continuedmentioning
confidence: 99%
“…One possible explanation for this observation is that CA-MRSA strains might preferentially colonize at nonnasal body sites. The throat and groin have been implicated as important sites of S. aureus and MRSA colonization among certain patient populations (8,9), and other studies have suggested that colonization patterns of CA-MRSA strains may be distinct from those of health care-associated MRSA strains (10,11). The epidemiology of community-associated S. aureus colonization and its role in subsequent infection are not well characterized in the United States.…”
mentioning
confidence: 99%
“…Indeed, many individuals with colonization in the throat or on the skin over the inguinal area have no colonization in the nasopharynx (5)(6)(7)(8). Small studies in the United States and elsewhere have demonstrated that S. aureus, and specifically the methicillin-resistant S. aureus (MRSA) genetic background USA300 can be found elsewhere on the body (reviewed in reference 4).…”
mentioning
confidence: 99%